1998
DOI: 10.1021/es980213c
|View full text |Cite
|
Sign up to set email alerts
|

Surface Oxidation of Pyrite as a Function of pH

Abstract: Pyrite, the most abundant metal sulfide at the surface of Earth, plays a key role in many processes such as acid mine drainage, redox cycling of metals at oxic-anoxic boundaries of lake bottom, and degradation of pollutants. The oxidation of pyrite was studied in batch experiments over a large range of pH (2.5-12), with trace oxygen. Surface analysis of the samples was performed using X-ray photoelectron spectroscopy (XPS). Speciation of the aqueous species was investigated by inductively coupled plasma atomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
150
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 280 publications
(177 citation statements)
references
References 38 publications
22
150
0
1
Order By: Relevance
“…Knipe et al (1995) said that the anomalous peak near 540 eV might be caused by adsorption of electrically isolated water clusters through hydrogen bonding. Bonnissel-Gissinger et al (1998) reported that extra peaks in O 1s spectra were observed at 535 ± 0.1 eV or 537.6 ± 0.1 eV as pyrite was oxidized by oxygen and formed islands of iron (hydr)oxides on the pyrite surface. In this study, however, we did not find evidence of iron (hydr)oxides, in spite of observing the oxidation of surface Fe(II).…”
Section: Characterization Of Arsenic-pyritementioning
confidence: 99%
See 2 more Smart Citations
“…Knipe et al (1995) said that the anomalous peak near 540 eV might be caused by adsorption of electrically isolated water clusters through hydrogen bonding. Bonnissel-Gissinger et al (1998) reported that extra peaks in O 1s spectra were observed at 535 ± 0.1 eV or 537.6 ± 0.1 eV as pyrite was oxidized by oxygen and formed islands of iron (hydr)oxides on the pyrite surface. In this study, however, we did not find evidence of iron (hydr)oxides, in spite of observing the oxidation of surface Fe(II).…”
Section: Characterization Of Arsenic-pyritementioning
confidence: 99%
“…Longer contact times resulted in larger peaks for Fe(III)-S and Fe(III)-O. In particular, the Fe(III)-O peaks at 710.3~712.3 eV are attributed to Fe(III) hydr(oxides) and the peak at 713.3 eV may be due to an Fe(III) multiplet structure (Bonnissel-Gissinger et al, 1998 Figure 51 shows the S 2p XPS spectra for mackinawite reacted with As(III) for various times. The major component of the S 2p spectra is located at ~161.9 eV and this peak is assigned to sulfide (S 2-) in mackinawite.…”
Section: Arsenic(v)removal and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…O 2 is an effective oxidant over a range of pH conditions; however, Fe 3+ is the dominant oxidant (reaction 1) at low pH (< 3.5) (Bonnissel Gissinger et al, 1998). Reactions 2 and 3 predominate at pH > 3.5, and reaction 3 dominates generally than reaction 2 at higher pH.…”
Section: Introductionmentioning
confidence: 96%
“…Due to its diverse roles in the natural and anthropogenic sulfur cycle, pyrite has been extensively studied in various experimental investigations of the kinetics of its dissolution and oxidation [9][10][11][12][13][14][15][16], the isotopic fractionations associated with these reactions [17][18][19][20][21][22], the microbiological processes involved [23][24][25], and the effect of pyrite surface reactivity and hydroxyl radical formation on human health [26][27][28][29]. Common to many of these studies is the pretreatment of pyrite to prevent experimental artifacts and inaccuracies.…”
Section: Introductionmentioning
confidence: 99%